The big three in economics Adam Smith, Karl Marx, and John Maynard Keynes - Skousen, Mark; Gale Group (Armonk, New York M.E. Sharpe, 2007)
Traces the turbulent lives and battle of ideas of the three most influential economists in world history: Adam Smith, representing laissez faire; Karl Marx, reflecting the radical socialist model; and John Maynard Keynes, symbolizing big government and the welfare state.
Adam Smith declares an economic revolution in 1776 -- From Smith to Marx: the rise and fall of classical economics -- Karl Marx leads a revolt against capitalism -- From Marx to Keynes: scientific economics comes of age -- John Maynard Keynes: capitalism faces its greatest challenge -- Conclusion: has Adam Smith triumphed over Marx and Keynes?.
Electronic reproduction.
Keywords: Smith, Adam -- 1723-1790.; Marx, Karl -- 1818-1883.; Keynes, John Maynard -- 1883-1946.; Economists -- History; Economics -- Philosophy; Economists -- Biography; Electronic books